Attitudes toward physical activities among college students - Kamarudin, Kamaria; Omar-Fauzee, Mohd. Sofian (National Institute of Psychology, Quaid-i-Azam University, Pakistan, 2007)
This study examined perceived benefits and barriers of physical activities among college students. Exercises Benefits/Barriers Scale (Sechrist, Walker, and Pender, 1987) was administered to 80 participants. Results indicated that the most common perceived benefits to physical activity for both female and male students were enjoyment of exercises, and decreased feelings of stress and tension. The female students also reported that exercise improves mental health, while for male students it improves strength. Among females students, the most common barrier to exercising is having no time to exercise, whereas for male students wanting to do other things with their time. Costly to exercise, lack of encouragement from family, taking too much time to exercise, and embarrassment are the other common barriers to physical activity.